2014
DOI: 10.1242/jeb.106161
|View full text |Cite
|
Sign up to set email alerts
|

Role of oleoylethanolamide as a feeding regulator in goldfish

Abstract: Oleoylethanolamide (OEA) is a bioactive lipid mediator, produced in the intestine and other tissues, which is involved in energy balance regulation in mammals, modulating feeding and lipid metabolism. The purpose of the present study was to investigate the presence and possible role of OEA in feeding regulation in goldfish (Carassius auratus). We assessed whether goldfish peripheral tissues and brain contain OEA and their regulation by nutritional status. OEA was detected in all studied tissues (liver, intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…significantly reduced both serum levels of TG and cholesterol without having any effect on HDL‐C and glucose levels . Levels of serum TG, but not glucose, were also reduced via OEA treatment (5 μg/g body weight) in goldfish, indicating the protective effects of OEA on TG levels in vertebrates . Fu et al reported increased PPAR‐α gene expression and other PPAR‐α target genes, including liver fatty‐acid binding protein (L‐FABP), uncoupling protein 2 )UCP‐2(, and FAT/CD36 after OEA administration (5 mg/kg, i.p.).…”
Section: Major Mechanisms Of Action Of Oea In the Management Of Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…significantly reduced both serum levels of TG and cholesterol without having any effect on HDL‐C and glucose levels . Levels of serum TG, but not glucose, were also reduced via OEA treatment (5 μg/g body weight) in goldfish, indicating the protective effects of OEA on TG levels in vertebrates . Fu et al reported increased PPAR‐α gene expression and other PPAR‐α target genes, including liver fatty‐acid binding protein (L‐FABP), uncoupling protein 2 )UCP‐2(, and FAT/CD36 after OEA administration (5 mg/kg, i.p.).…”
Section: Major Mechanisms Of Action Of Oea In the Management Of Nafldmentioning
confidence: 99%
“…OEA plays a pivotal role in lipid metabolism by modulating lipids in circulation and tissues in addition to its satietogenic effect . Several experimental studies have shown the useful effects of OEA on lipid profiles (Supplemental Table 1) . Further investigations have indicated that the lipolytic activity of OEA and its effects on fatty acid mobilization by activating PPAR‐α and PPAR‐α target genes contribute to lipid metabolism .…”
Section: Major Mechanisms Of Action Of Oea In the Management Of Nafldmentioning
confidence: 99%
“…Third, viral-mediated enhancement of OEA production in rat jejunum reduces food intake and concomitantly increases local expression of PPAR-a target genes (Fu et al, 2008). Finally, OEA levels in small intestine from various vertebrate species, including fish, snakes, and rodents, rise from %50 nM in the fasting state to R250 nM after feeding (Astarita et al, 2006b;Fu et al, 2007;Tinoco et al, 2014;Igarashi et al, 2017), a concentration range that is compatible with PPAR-a activation (Fu et al, 2003;Astarita et al, 2006a). In sum, the available data indicate that OEA is a physiologically relevant endogenous agonist for small-intestinal PPAR-a, which participates in the control of satiety .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, from the cumulative evidence in humans and rodents and work done by Tinoco and colleagues , it is worth noting that a strong association between OEA and other feeding regulators exists imparting the satiating/anorexic properties. Therefore, future studies are required to clarify the satiating efficacy of OEA alone by performing studies using knock‐out animal models for specific receptors involved in inducing satiation.…”
Section: Relationship Between Oleoylethanolamide and Feeding Regulatimentioning
confidence: 98%